Religia online, czyli o procesie wirtualizacji religii = RELIGION ONLINE, COMMENTS ON THE PROCESS OF VIRTUALIZATION OF RELIGION - Przybył-Sadowska, Elżbieta (Studia religiologica, 2007)
The article constitutes an attempt to describe the functioning of religion in the Internet, and particularly of the religious practices which are conducted online. The authoresses of the article trace the transformations which have taken place in the use of the Internet as an instrument employed to conduct types of practices, beginning with the simplest communicators, through the use of videoconfer ences, up to the use of three-dimensional techniques. Special attention was devoted to virtual temples, that is those Internet sites where one can make a virtual sacrifice to a deity. In the article, the authoresses also draw attention to the ways of conducting these types of rituals and they present the views thanks to which the participants of these events may have an impression that they are actually taking part in religious practices, rather than just participating in a game. The article closes with an analysis of the ways of functioning of religion in the virtual worlds, with particular attention being drawn to the Second Life, which has become immensely popular in recent times. Apart from traditional religions which open up their sites of worship in Second Life, there also arise new cults in this world which are characteristic exclusively of ritualistic reality. The fundamental problem which has to be faced here by scholars is an attempt to answer the question, to what extent these are really new religious movements and to what extent they constitute an element of internet games and instruments which these games make use of.